Core-Periphery Relations and Organization Studies - Westwood, R.; Westwood, R.; Jack, G.; Jack, G.; Khan, F.; Khan, F.; Frenkel, M.; Frenkel, M. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Core-Periphery Relations and Organization Studies draws together postcolonial and indigenous thinking through the conceptual lens of core-periphery relations to advance debate in organization studies. A particular aim of this book is to broaden, deepen and critically reassert a postcolonial imagination in this domain.